Potensi dan Peluang Akomodasi Alternatif Glamour Camping (Glamping) di Kawasan Destinasi Pariwisata Sembalun Kabupaten Lombok Timur - Antoni, Yoyok (Universitas Mataram, 2024)
The aim of the research carried out was to determine the potential and opportunities for the availability of alternative Glamping accommodation in the Sembalun tourism destination area, East Lombok district, as well as to determine the calculation of Location Quotient (LQ), Specialization Index, Shift Share and Net Shift (PB) in analyzing the potential and opportunities for provision. alternative accommodation. The research methodology used in this research is a type of descriptive quantitative research based on the calculation of the Specialization Index, Location Quotient (LQ), and Shift Share. With a rational-comprehensive approach. Types and sources of data in this research, primary and secondary data, with data collection techniques in literature and direct observation or observations. The results of this research show that the specialization index calculation for 17 (seventeen) sectors based on current prices obtained values ​​of 0.31; 0.30 and 0.26. Meanwhile, based on constant prices, the IS value obtained for 3 (three) years was 0 .62; 0.54; 0.46, the value of the specialization index is close to one. For the combined calculation of LQ and Net Shift, it is known that the accommodation, food and drink provision sector have a value of LQ > 1, and PB > 1, which means that the agricultural sector in a broad sense is based on current and constant prices. for 3 years has a stable LQ value which means the potential and opportunities to build and develop accommodation in tourism destinations, are still quite large.